True Dreams in Hadith: An Authenticity Critique and Its Implications for Islamic Spirituality - Zaini, Muhammad (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2025)
Abstract This article examines the hadith of the Prophet Muhammad (peace be upon him) about ar-ru'yā al-ḥasanah (true dreams) with a focus on analyzing the validity of sanad and matan as well as the meaning of the hadith through the sharḥ al-ḥadīṡ approach. In the Islamic thought, dreams are understood through two main tendencies: first, as a transcendent phenomenon related to the supernatural dimension and potentially a means of conveying divine signals; Second, as a psychological phenomenon that is subjective and has no theological significance. These differences of view require a critical and methodological study of hadith so that the understanding of dreams does not exceed the limits of the authority of Islamic teachings. This research uses a qualitative approach based on library research, with primary data sources in the form of authoritative hadith books, especially Sunan Ibn Mājah, as well as supporting literature in the field of hadith science. Data analysis is carried out through the stages of hadith takhrīj, i'tibār sanad, sanad criticism, and matan criticism, then followed by textual and contextual analysis of the meaning of hadith. The results of the study show that the hadith about ar-ru'yā al-ḥasanah narrated by Ibn Mājah is ṣaḥīḥ quality from the aspects of sanad and matan and strengthened by the narration in other primary hadith books. The content of the hadith emphasizes that true dreams are part of al-mubasysyirāt (good news) which is personal and non-normative and cannot be equated with prophetic revelation. Thus, this hadith provides a theological foundation in understanding the phenomenon of dreams in Islam. Abstrak Artikel ini mengkaji hadis Nabi SAW tentang ar-ru’yā al-ḥasanah (mimpi yang benar) dengan fokus pada analisis validitas sanad dan matan serta pemaknaan hadis melalui pendekatan syarḥ al-ḥadīṡ. Dalam khazanah pemikiran Islam, mimpi dipahami melalui dua kecenderungan utama: pertama, sebagai fenomena transenden yang berkaitan dengan dimensi gaib dan berpotensi menjadi sarana penyampaian isyarat ilahi; kedua, sebagai fenomena psikologis yang bersifat subjektif dan tidak memiliki signifikansi teologis. Perbedaan pandangan tersebut menuntut kajian hadis yang kritis dan metodologis agar pemahaman terhadap mimpi tidak melampaui batas otoritas ajaran Islam. Penelitian ini menggunakan pendekatan kualitatif berbasis studi kepustakaan (library research), dengan sumber data primer berupa kitab-kitab hadis otoritatif, khususnya Sunan Ibn Mājah, serta literatur pendukung dalam bidang ilmu hadis. Analisis data dilakukan melalui tahapan takhrīj hadis, i‘tibār sanad, kritik sanad, dan kritik matan, kemudian dilanjutkan dengan analisis pemaknaan hadis secara tekstual dan kontekstual. Hasil penelitian menunjukkan bahwa hadis tentang ar-ru’yā al-ḥasanah yang diriwayatkan oleh Ibn Mājah berkualitas ṣaḥīḥ dari aspek sanad dan matan, serta diperkuat oleh periwayatan dalam kitab hadis primer lainnya. Kandungan hadis tersebut menegaskan bahwa mimpi yang benar merupakan bagian dari al-mubasysyirāt (kabar gembira) yang bersifat personal dan non-normatif, serta tidak dapat disetarakan dengan wahyu kenabian. Dengan demikian, hadis ini memberikan landasan teologis yang proporsional dalam memahami fenomena mimpi dalam Islam.